2018
DOI: 10.1093/infdis/jiy477
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Prefusion F Immunoglobulin G as a Correlate of Protection Against Respiratory Syncytial Virus Acute Respiratory Illness

Abstract: BackgroundTransplacental respiratory syncytial virus (RSV) antibody transfer has been characterized, but little is known about the protective effect of breast milk RSV-specific antibodies. Serum antibodies against the prefusion RSV fusion protein (pre-F) exhibit high neutralizing activity. We investigate protection of breast milk pre-F antibodies against RSV acute respiratory infection (ARI).MethodsBreast milk at 1, 3, and 6 months postpartum and midnasal swabs during infant illness episodes were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 45 publications
3
49
0
1
Order By: Relevance
“…A study from South Africa found that breastmilk sIgA against GBS was associated with lower risk for GBS LOD in young infants (229). In a study from Nepal, breastmilk RSV IgG levels, but not IgA levels, were lower in mothers of infants with RSV acute respiratory infection (230). While these studies report potential association between breastfeeding and reduction in disease risk, the casual relationship has not been confirmed.…”
Section: Induction Of Vaccine-specific Immunity In Breastmilkmentioning
confidence: 93%
“…A study from South Africa found that breastmilk sIgA against GBS was associated with lower risk for GBS LOD in young infants (229). In a study from Nepal, breastmilk RSV IgG levels, but not IgA levels, were lower in mothers of infants with RSV acute respiratory infection (230). While these studies report potential association between breastfeeding and reduction in disease risk, the casual relationship has not been confirmed.…”
Section: Induction Of Vaccine-specific Immunity In Breastmilkmentioning
confidence: 93%
“…The palivizumab (IgG, IgA, and sIgA) and naturally-occurring RSV F protein-specific (IgG and sIgA/IgA) concentrations in gastric and intestinal samples and ex-vivo-incubated samples were quantified by ELISA as described by Mazur et al [14] with modifications. Nunc MaxiSorp 96-well plates (Thermo Scientific, Waltham, MA, USA) were coated at 4 • C overnight with 100 µL of 100 ng/mL human RSV pre-fusion F protein (Sino Biological, Wayne, PA, USA).…”
Section: Rsv F Protein-specific Elisamentioning
confidence: 99%
“…[16][17][18] Many of the health-promoting effects of breastfeeding are due to the provision of passive immunity via immunoglobulins and other bioactive factors (e.g., lactoferrin), and previous studies have shown that milk-borne antibodies are produced in response to viral infection. [19][20][21][22] However, few studies have examined the presence of antibodies to SARS-CoV-2 in human milk. 23,24 In one recent study, milk from 12 of 15 women previously infected with SARS-CoV-2 contained IgA that was reactive to the receptor binding domain (RBD) of the SARS-CoV-2 spike protein.…”
Section: Introductionmentioning
confidence: 99%